2020
DOI: 10.1111/rda.13623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the factors that affect the pregnancy rates during embryo transfer in beef heifers

Abstract: The aim of this study was to evaluate the effects of the transfer side, transfer location, cervix transfer score, type and diameter of corpus luteum (CL) during embryo transfer on pregnancy rates in beef heifers. Progesterone‐based synchronization and superovulation protocol were applied to Simmental cows used as donors (n = 168). Uterine flushings were performed on day 7 following artificial insemination. Obtained Code I (excellent or good) and II (fair) quality embryos were transferred to recipient beef heif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…That one or more of insults to the reproductive tract are potentially deleterious to pregnancy establishment is indicated by observations that the difficulty in passing the cervix and depositing the embryo in the uterus is negatively associated with P/ET ( Jaśkowski et al, 2010 ; Kasimanickam et al, 2018 , 2019 ; Alkan et al, 2020 ). Moreover, the physical characteristics of the transfer instrument have been reported to affect pregnancy success.…”
Section: Causes Of Pregnancy Loss Associated With Etmentioning
confidence: 99%
“…That one or more of insults to the reproductive tract are potentially deleterious to pregnancy establishment is indicated by observations that the difficulty in passing the cervix and depositing the embryo in the uterus is negatively associated with P/ET ( Jaśkowski et al, 2010 ; Kasimanickam et al, 2018 , 2019 ; Alkan et al, 2020 ). Moreover, the physical characteristics of the transfer instrument have been reported to affect pregnancy success.…”
Section: Causes Of Pregnancy Loss Associated With Etmentioning
confidence: 99%
“…Nevertheless, other research papers reported that increase in the concentration of P4 in accordance with the corpus luteum increase in crossbred recipients and according to Binelli et al, (2001), larger corpus luteum in recipients may increase pregnancy rates in embryo transfer programs. On the other hand, Alkan et al, (2020) reported that cavity-containing corpora lutea resulted in higher pregnancy rates in heifers receiving fresh in vivo produced embryos. In addition, that, Szelenyi et al, (2019) found that pregnancy losses in Holstein-Friesian cows examined by ultrasonography between days 29-42 after insemination were higher among cows with cavity-containing corpora lutea The present investigation cleared that PR/ET was significantly higher in embryo recipient Holstein heifers in which estrus or heat was induced using PGF2 alpha, as compared to recipient heifers with spontaneous heat.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo transfer technology is an important breeding technique which aids in fortification of genetic superiority of cattle herds for both improved production and reproduction with potential improvement of farm economics (Dochi, 2019;Alkan et al, 2020). Multiple studies have been conducted to elucidate factors affecting pregnancy establishment in embryo recipient heifers and cows after transfer of in vivo or in vitro produced embryos (Block et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations